2013
DOI: 10.1111/j.1532-950x.2013.12039.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute adverse events associated with ventral slot decompression in 546 dogs with cervical intervertebral disc disease

Abstract: AE occurred in 9.9% of dogs that had VSD, and were significantly associated with perioperative hypotension, C7-T1 disc extrusions, surgeon experience, and NSAID usage. Identification of a major postoperative AE is an indication for immediate diagnostic imaging studies, as 50% of dogs experiencing major AE required reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(123 citation statements)
references
References 41 publications
6
109
3
5
Order By: Relevance
“…Nonetheless, a single study comparing thoracolumbar Hansen type I IVDH in FB and Dachshunds showed that FBs were younger at the time of surgery [28], even if the number of FBs was limited in this report ( n  = 47). Similarly, studies addressing cervical IVDH revealed a median age ranging between 6 and 8 years old in chondrodystrophic dogs [25, 26, 31]. One hypothesis for this difference could be the fact that intervertebral disk degeneration occurs faster in FB than in other chondrodystrophic breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a single study comparing thoracolumbar Hansen type I IVDH in FB and Dachshunds showed that FBs were younger at the time of surgery [28], even if the number of FBs was limited in this report ( n  = 47). Similarly, studies addressing cervical IVDH revealed a median age ranging between 6 and 8 years old in chondrodystrophic dogs [25, 26, 31]. One hypothesis for this difference could be the fact that intervertebral disk degeneration occurs faster in FB than in other chondrodystrophic breeds.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs with cervical IVDH a similar occurrence of neurogenic hypoventilation was recently found to affect 2 of 35 tetraplegic cases. 55 In one report on acute cervical hydrated nucleus pulposus extrusion between C3 and C6, 3 of 10 dogs developed respiratory dysfunction and 1 subsequently died. 56 …”
Section: Respiratory Dysfunction Following Spinal Cord Injurymentioning
confidence: 98%
“…It allows a reduction in the inflammatory cascade and promotes the granulation tissue formation and epithelialization and may be applied to human medicine since the incidence of postsurgical infections is 1 to 2.4% (Cross, 2014;Medina, 2013;Newark, 2012; Kirkby K. , 2014; Rossmeisl, White, et al, 2013).…”
Section: Lasertherapy and Locomotor Training In Quadruped Animalsmentioning
confidence: 99%